2008
DOI: 10.1007/s10620-007-0180-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effects of Rebamipide According to Helicobacter pylori Status in Patients with Chronic Erosive Gastritis: A Randomized Sucralfate-Controlled Multicenter Trial in China—STARS Study

Abstract: The aim of the study was to investigate the effects of rebamipide on symptom, histology, endogenous prostaglandin, and mucosal oxygen free radicals in chronic erosive gastritis (CEG) patients by using sucralfate as a control. The trial also examined whether Helicobacter pylori infection would affect rebamipide-induced protection. A total of 453 endoscopy-confirmed CEG patients from 11 hospitals in China were enrolled in the study. They randomly received either rebamipide (100 mg t.i.d) or sucralfate (1.0 t.i.d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
(25 reference statements)
2
19
0
5
Order By: Relevance
“…Furthermore, we detected decreased levels of Rothia, Granulicatella, Streptococcus, Fusobacterium, Gemella, Haemophilus, Neisseria, and Porphyromonas in CEG patients with YTC. All of these 8 genera have been described in normal populations of healthy oral microbiota45678910111213141516171819202122232425262728293031. An increasing trend in these bacteria was observed after therapy, albeit not statistically significant (Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, we detected decreased levels of Rothia, Granulicatella, Streptococcus, Fusobacterium, Gemella, Haemophilus, Neisseria, and Porphyromonas in CEG patients with YTC. All of these 8 genera have been described in normal populations of healthy oral microbiota45678910111213141516171819202122232425262728293031. An increasing trend in these bacteria was observed after therapy, albeit not statistically significant (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Chronic erosive gastritis (CEG) is a very common gastrointestinal disease in China12. Patients with CEG always present with various gastrointestinal tract symptoms and histological changes in gastric mucosa leading to decreased quality of life13. Currently, TCM practitioners often use Chinese herbal medicines to successfully treat gastrointestinal disorders categorized as damp-heat syndrome (i.e., CEG, enteritis, gastric ulcer, and gastralgia), which is mainly characterized by YTC14.…”
mentioning
confidence: 99%
“…In a recent multicenter randomized clinical trial (RCT), rebamipide (Mucosta; Otsuka Pharmaceutical, Tokyo, Japan) was reported to be efficacious for the treatment of large gastric ulcers after Helicobacter pylori eradication [9]. In randomized controlled studies, rebamipide prevented nonsteroidal anti-inflammatory drug (NSAID)-induced peptic ulcers, accelerated gastric ulcer healing, and suppressed mucosal inflammation in chronic erosive gastritis [10][11][12]. The action of rebamipide is explained at least in part by the increased expression of epidermal growth factor (EGF) and EGF receptors on epithelial cells [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Another recent placebo-controlled trial also found that rebamipide is as effective as omeprazole in treating H. pylori-positive gastric ulcers after eradication (5). In randomized controlled studies, rebamipide has been found to prevent nonsteroidal anti-inflammatory drug (NSAID)-induced peptic ulcers, accelerate gastric ulcer healing and suppress mucosal inflammation in patients with chronic erosive gastritis (6,7). Recently, several studies (8)(9)(10)(11)(12)(13)(14) have examined the efficacy of rebamipide and PPI combination therapy for the treatment of ESD-induced ulcers.…”
Section: Introductionmentioning
confidence: 99%